EFEKTIVITAS KONSELING GIZI DENGAN MEDIA BUKU SAKU TERHADAP PENGETAHUAN, SIKAP MENGENAI PENCEGAHAN HIPERTENSI, DAN KEBIASAAN MAKAN NATRIUM DAN SERAT PADA REMAJA DI SMAN 15 SEMARANG - Bella Amalia Hapsari; Yuniarti Yuniarti; Enik Sulistyowati (Poltekkes Kemenkes Semarang, 2015)
Background : Hypertension is common in adults but hypertension now occurs in adolescents. Prevalence of hypertension according to Semarang City Health Office teen age group has increased from 6,01% (2009) to 8,7% (2013). Preliminary survey with blood pressure measurement on 60 adolescents at SMAN 15 Semarang, 43,3% high blood pressureObjective : To know the effectiveness of nutritional counseling with pocket book media to knowledge, attitude about hypertension prevention, sodium and fiber feeding habit in adolescents at SMAN 15 Semarang. Method : Clinical nutrition study with quasi experimental research type and randomized pre and post test group control design. Number of sampelts 20 treatments and 20 controls. Data collected were data of knowledge, attitude, eating habits of sodium and fiber. The analysis used to test the average difference in the treatment and control group using the Independent t-test. Results: The result of post test of knowledge of treatment group 100% good and control group 30% good. Post test attitude of treatment group 55% support and control group 50% support. Post test feeding habits sodium treatment group 55% good and control group 10% good. Post test feeding habits fiber group treatment 25% good and control group 10% good.Conclusion: Nutrition counseling with pocket book is effective to improves knowledge and eating habits of sodium but is not effective at improving fiber eating attitudes and habits. Efforts to prevent hypertension need to be done cooperation between BK with Local Health Center to do filtering especially hypertension.